2015
DOI: 10.1063/1.4935988
|View full text |Cite
|
Sign up to set email alerts
|

Twist-controlled resonant tunnelling between monolayer and bilayer graphene

Abstract: We investigate the current-voltage characteristics of a field-effect tunnelling transistor comprised of both monolayer and bilayer graphene with well-aligned crystallographic axes, separated by three layers of hexagonal boron nitride. Using a self-consistent description of the device's electrostatic configuration we relate the current to three distinct tunable voltages across the system and hence produce a two-dimensional map of the I-V characteristics in the low energy regime. We show that the use of gates ei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…We attribute this to a large twist angle (≈ 5º) which shifts VHS to above 0.4 eV, higher than the chemical potential (~ 0.2 eV) in tBGr we can reach by applying gate and bias voltages. ) with modified electrostatic model considering AB stacking bilayer graphene as the top electrode [25]:…”
Section: Resultsmentioning
confidence: 99%
“…We attribute this to a large twist angle (≈ 5º) which shifts VHS to above 0.4 eV, higher than the chemical potential (~ 0.2 eV) in tBGr we can reach by applying gate and bias voltages. ) with modified electrostatic model considering AB stacking bilayer graphene as the top electrode [25]:…”
Section: Resultsmentioning
confidence: 99%
“…In the case of graphene, studies of its role as a barrier in magnetic tunnel junctions [35][36][37] and between metal contacts [38,39] showed that it behaves as a strong out-of-plane insulator. In fact, in experiments conducted in the absence of a magnetic field and in the presence of a field parallel to the graphene layers, the measured tunnelling current has been well described by assuming that all tunnelling from the further BLG layer is suppressed [10,12]. For this reason, here, we take the limit c = c, corresponding to the decay through graphene being significant and similar to that through hexagonal boron nitride.…”
Section: Device Description and Tunnelling Matrix Elementmentioning
confidence: 99%
“…Gr/BN/Gr structures display negative differential resistance (NDR), 20,24,27,[30][31][32]34 and theoretical calculations predict maximum frequencies of several hundred GHz. 26 The NDR arises from the line-up of the source and drain graphene Dirac cones combined with the conservation of in-plane momentum.…”
Section: Introductionmentioning
confidence: 99%
“…In one experiment in which plateaus were observed in the current-voltage characteristics instead of NDR, the experimental results could be matched theoretically by ignoring momentum conservation. 23 In the theoretical treatments, the focus has been primarily on the rotation between top and bottom graphene layers and the resulting misalignment of the Dirac cones 20,27,32 . Recently, the effect of misalignment of both the BN and the graphene layers including the effects of phonon scattering have been investigated using the low-angle effective continuum model 30,35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation